PENGARUH TEMPERATUR TUANG TERHADAP POROSITAS, STUKTUR MIKRO DAN KEKERASAN DARI ALUMUNIUM WAJAN NAGARA DAN WAJAN JAWA MENGGUNAKAN PENGECORAN EVAPORATIF - Yuono, Nanang; Siswanto, Rudi (Universitas Lambung Mangkurat, 2022)
Aluminum and its alloys are the second largest metal materials used after steel. Applications and aluminum alloys are very diverse ranging from building vehicle bodies engine components components to ships to applications on airplanes. The strength and hardness of high aluminum alloys,one of the applications of aluminum as a component in the motor is as an ingredient for making alloy wheels, more specifically aluminum alloys. Used aluminum can be obtained from the remnants of the industry making aluminum doors, windows and frames, making aluminum shelves and storefronts, and other products with aluminum profiles as the main material. many of them use aluminum scrap as their main casting material to reduce production costs. Evaporative or casting casting using Styrofoam or a lost foam casting pattern is a casting using a material pattern that can evaporate when exposed to molten metal heat. Casting uses a temperature of 650 ° C, 700 ° C, 750 ° C, 800 ° C. The results of casting temperatures can affect porosity, microstructure, and hardness.